Highly efficient MXene/Nano-Cu smoke suppressant towards reducing fire hazards of thermoplastic polyurethane. (November 2021) - Shi, Yongqian; Liu, Chuan; Fu, Libi; Feng, Yuezhan; Lv, Yuancai; Wang, Zixiao; Liu, Minghua; Chen, Zhixin
Graphical abstract: Highlights: Nano-Cu was uniformly distributed in Ti3 C2 Tx nanosheets for Ti3 C2 Tx /Nano-Cu hybrid. TPU/MXene hybrid showed markedly reduced smoke production rate. TPU/MXene hybrid exhibited ultra-low CO production rate and total CO yield. Reduced fire hazards are attributed to multiple effects of Ti3 C2 Tx /Nano-Cu hybrid. Abstract: A large number of toxic fumes evolved from polymeric materials are a great threat to human evacuation. The aim of this work is to dramatically reduce the generation of smoke and toxic gaseous products upon polymers burning. A highly efficient titanium carbide/nano-copper (Ti3 C2 Tx /Nano-Cu) hybrid smoke suppressant was synthesized by interficial adhesion and then incorporated into thermoplastic polyurethane (TPU) to fabricate TPU nanocomposites. The Ti3 C2 Tx /Nano-Cu hybrid was homogeneously dispersed in the TPU matrix and showed a strong interfacial interaction with the TPU host. Introducing the Ti3 C2 Tx /Nano-Cu hybrid into TPU led to enhanced high-temperature stability. Furthermore, the smoke production rate, CO production rate and total CO yield of the TPU nanocomposite containing 2 wt% Ti3 C2 Tx /Nano-Cu hybrid decreased by 66.7%, 51.8% and 52.9%, respectively, compared with those of pure TPU. The reduced fire hazards of the TPU were due to the physical barrier, the catalytic charring and the chemical conversion of Ti3 C2 Tx /Nano-Cu hybrid.